Information on lifestyle habits of individuals with COVID-19 worldwide: Review of literature - Silva Junior, Luiz Carlos Francelino; Santana, Gibson; Mesquita, Rodrigo; Oliveira, Tatiana; Arnozo, Gabriel; Santos, Aisla; Silva Filho, Etvaldo; Santana, Fernanda; Aquino, Saulo; Cunha, Euclides; Albuquerque, Antônio; Alcântara, Rafaela (Revista Portal: Saúde e Sociedade, 2021)
Background: COVID-19 is a respiratory disease that appeared in China in late 2019 and soon spread around the world, causing a pandemic. Aims: This is study sought to systematize information about life habits in epidemiological studies in patients with COVID-19. Methods: This is a systematic review conducted according to the Preferred Reporting Items for Systematic Reviews and Meta-Analyzes (PRISMA) recommendations. We selected articles published in PubMed, Medline and Scopus database between January 1 and April 24, 2020, using the descriptors COVID-19, SARS-CoV-2, 2019-nCoV, n-CoV and coronavirus combined with clinical profile and epidemiology. In this study, we sought to identify characteristics about patients' lifestyle habits: smoking (current or previous), alcohol consumption and physical activity. Results: We analyzed 7489 scientific studies, of which 158 had clinical and epidemiological variables, amounting 100.0563 patients. 30 studies included lifestyle habits (8,323 individuals) from five countries: Brazil, China, Korea, Spain and USA (593). A percentage of 56.5% (n = 4624) were men and 44.4% (n = 3687) women. Among the variables, smoking (current or previous) was present in 30 investigations; alcohol consumption in four and physical activity was not observed in any article. The highest smoking rates were observed in the USA (21.79%) and Spain (18.75%). Alcohol consumption was 7.73%. Being higher in Brazil (17.28%). Conclusions: New studies on the epidemiological and clinical aspects of COVID-19 include variables about lifestyle, especially smoking, alcohol consumption and physical activity. This information may offer future knowledge about the factors of illness and severity of COVID-19 in the population. Keywords: Risk factors. Coronavirus infection. Systematic review.